Implementation of triple bottom line to a business model canvas in reverse logistics - Wit, Bogdan; Pylak, Korneliusz (Electronic Markets, 2020)
Waste generation, especially hazardous waste, can strongly affect the environment and human lives. There is an urgent need to implement sustainable hazardous waste management tools to reduce their harmful impact on the environment stemming from incorrect waste management. However, there is still a lack of business model concepts combining sustainable development and risk management in reverse logistic value chains for hazardous waste. Therefore, the authors develop a novel sustainable business model canvas for both an entity and the logistics system using the Osterwalder's Business Model Canvas integrated with the concept of sustainable development in economic, social and environmental areas (Triple Bottom Line, TBL) and risk-related elements. Then, using the developed sustainable business model canvas, the model for the logistics system for the treatment of hazardous waste containing asbestos was successfully created. The model was implemented in the prototype of computer software in the form of electronic network services.
Place: Heidelberg Publisher: Springer Heidelberg WOS:000531754400001
Keywords: Informatique; Innovation logistique; Réservé UdeM; numérique